Cost-Effectiveness Analysis of Imaging Modalities for Breast Cancer Surveillance Among BRCA1/2 Mutation Carriers: A Systematic Review - Li, Jiaxin; Jia, Ziqi; Zhang, Menglu; Liu, Gang; Xing, Zeyu; Wang, Xin; Huang, Xin; Feng, Kexin; Wu, Jiang; Wang, Wenyan; Wang, Jie; Liu, Jiaqi; et al. (Frontiers in Oncology, 2022)
Abstract BACKGROUND: BRCA1/2 mutation carriers are suggested with regular breast cancer surveillance screening strategies using mammography with supplementary MRI as an adjunct tool in Western countries. From a cost-effectiveness perspective, however, the benefits of screening modalities remain controversial among different mutated genes and screening schedules. METHODS: We searched the MEDLINE/PubMed, Embase, Cochrane Library, Scopus, and Web of Science databases to collect and compare the results of different cost-effectiveness analyses. A simulated model was used to predict the impact of screening strategies in the target group on cost, life-year gained, quality-adjusted life years, and incremental cost-effectiveness ratio (ICER). RESULTS: Nine cost-effectiveness studies were included. Combined mammography and MRI strategy is cost-effective in BRCA1 mutation carriers for the middle-aged group (age 35 to 54). BRCA2 mutation carriers are less likely to benefit from adjunct MRI screening, which implies that mammography alone would be sufficient from a cost-effectiveness perspective, regardless of dense breast cancer. CONCLUSIONS: Precision screening strategies among BRCA1/2 mutation carriers should be conducted according to the acceptable ICER, i.e., a combination of mammography and MRI for BRCA1 mutation carriers and mammography alone for BRCA2 mutation carriers. (PROSPERO, CRD42020205471)